5) Calcule a equação: 0 = -3x + 1 - x - 7x + 10x - 15
Soluções para a tarefa
Respondido por
1
-3x + 1 - x - 7x + 10 x - 15 = 0
organizando letra com letra e numero com numero
-3x - x - 7x + 10x = 15 -1
-4x - 7x + 10x = 15 - 1
-11x + 10x = 14
-x = 14 (.1)
x = - 14
Respondido por
1
Resposta:
x = -14
Explicação passo-a-passo:
-3x + 1 - x - 7x + 10 x - 15 = 0
organizando letra com letra e numero com numero
-3x - x - 7x + 10x = 15 -1
-4x - 7x + 10x = 15 - 1
-11x + 10x = 14
-x = 14 (.1)
x = - 14
Perguntas interessantes
Matemática,
8 meses atrás
Matemática,
8 meses atrás
Português,
8 meses atrás
Biologia,
10 meses atrás
Física,
1 ano atrás
Inglês,
1 ano atrás